Precision calculation of the axion-nucleon coupling in chiral perturbation theory - Thomas Vonk; Feng-Kun Guo; Ulf-G. Meißner (Journal of High Energy Physics, 2020)
Abstract We derive the axion-nucleon interaction Lagrangian in heavy baryon chiral perturbation theory up to next-to-next-to-leading order. The effective axion-nucleon coupling is calculated to a few percent accuracy.